Occupational exposure to chemicals in the construction of buildings - Hernández-Gómez, Gabriela (2012)
Objectives: (i) To estimate occupational exposure levels to chromium, manganese and iron fumes, and from wood dust in tasks related to building construction. (ii) To propose an occupational exposure matrix to agents in study. Materials and methods: An exploratory study was carried including nine construction projects from five companies. Analytical Methods were based on documents: OSHA ID121 and MDHS 14/03. Occupational exposure levels to the chemical agents were compared to the threshold limit values of the national standard INTE 31-08-04-01. Influence of some possible determinants of exposure by statistical association tests was calculated. Results: Mean for occupational exposure levels of inhalable wood dust was 3.55 mg/m3; relationship was found between sampling time and the concentrations. Chromium was not detected in collected samples. Mean for iron was 0.78 mg/m3; no relationship was found between concentration values and possible exposure determinants. Mean for manganese concentration was 0.04 mg/m3; temperature was the most influential factor. Conclusions: Occupational exposure levels for iron, manganese and inhalable wood dust were different among projects and companies. Dust concentrations were associated with sampling time and no statistical significance was found for metal exposure determinants.